Ready for Growth : Solutions to Increase Access to Finance for Women-Owned Businesses in the Middle East and North Africa - World Bank (Washington, DC, 2013)
The Middle East and North Africa (MENA) region is at one of the most critical turning points in its modern history. The Arab spring was driven by the desire for economic opportunity and justice in the face of poverty and unemployment. The development of strong economies that enable both women and men to enhance their livelihoods is crucial for the future of the region. The growth and success of women-owned businesses is one of the most profound changes in the business world today. There is no doubt that women are an emerging market force. However, many businesswomen are not accessing commercial credit, an essential driver of business success. Lack of access to finance and financial services is repeatedly identified as the major constraint for women business owners. This report 'ready for growth: solutions to increase access to finance for women-owned business in the Middle East and North Africa', is designed to shed a light on those barriers. It is the result of a unique International Finance Corporation (IFC) partnership with vital voices and the Middle East and North Africa Businesswomen's Network (MENA BWN). Its purpose is to fill a critical gap in our knowledge of what women-owned businesses need in terms of financial products and services. Building on our knowledge of how commercial banks currently reach the women's market, this survey data can provide banks in MENA with information to better serve women business owners.